Complementary description of Oithona (Paroithona) parvula (Farran, 1908), (Cyclopoida, Oithonidae) and its distribution in the Adriatic Sea, Mediterranean - Kršinić, Frano (Zootaxa, 2026)
The female of the cyclopoid copepod Oithona (Paroithona) parvula (Farran, 1908) is complementary described, and the male is described for the first time from samples collected in the Adriatic Sea. The Adriatic specimens differ from the original description in several morphological characteristics, such as; number of antennule segments and setae, number of setae on second antennary segment, the maxillule endopodite, in the maxilla, the first maxilliped segment, leg 5 and the numbers of spines on the exopodal segment of leg 4. A key to identify males and females of Adriatic species of Oithona is herein provided. As a glacial relic, the species O. parvula is permanently present in the northern Adriatic depression, and in the Jabuka Pit from a depth of 50 m to the bottom, with the presence of North Adriatic Dense Water. This water mass is an important habitat for O. parvula and plays a key role in its transport and distribution along the western Adriatic and southern Adriatic Pit.